2010
DOI: 10.1016/j.thromres.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The “normal” factor VIII concentration in plasma

Abstract: Introduction The quantitation of factor (F)VIII by activity-based assays is influenced by the method, procedure, the quality and properties of reagents used and concentrations of other plasma proteins, including von Willebrand factor (VWF). Objective To compare FVIII concentrations measured by activity-based assays with those obtained by an immunoassay and to establish the influence of plasma dilution on the FVIII clotting activity (FVIIIc). Methods The APTT, a chromogenic assay (Coatest) and two in-house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…In this study, mean concentrations were respectively 0.4±0.4 IU/mL for factor VIII, and 0.3±0.2 IU/mL for factor IX. Our values are lower than mean concentrations of factors VIII and IX, reported in the literature [12,17,18], which varies between 0.7 and 1 IU/mL for factor VIII. This difference could be due to the methods of plasma preparation.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, mean concentrations were respectively 0.4±0.4 IU/mL for factor VIII, and 0.3±0.2 IU/mL for factor IX. Our values are lower than mean concentrations of factors VIII and IX, reported in the literature [12,17,18], which varies between 0.7 and 1 IU/mL for factor VIII. This difference could be due to the methods of plasma preparation.…”
Section: Discussioncontrasting
confidence: 76%
“…17 It was however below the frequency found for strong immunogens, such as KLH, 15,18 and it was too low to be detected without any in vitro culture phase. The data suggest that the basal level of expression of endogenous FVIII (ie, 0.1 mg/mL or 0.3 nM in normal plasma 19 ) does not preclude a large escape of FVIII-specific CD4 T cells from negative thymic selection. Whether such a large pool of circulating FVIII-specific CD4 T cells provides help to natural FVIII-specific B cells and accounts for the presence of natural anti-FVIII antibodies in a substantial percentage of healthy individuals 3,20 and whether the uncontrolled recruitment of this pool leads to the development of acquired hemophilia remain to be established.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have shown that VWF in the FVIII‐deficient plasmas utilized in one‐stage aPTT assays appears to depress measurements of apparent FVIII activity [23–25]. We wanted to determine whether similar effects were present when inhibitor titers were calculated using a chromogenic assay to measure residual FVIII activity.…”
Section: Discussionmentioning
confidence: 99%